Pengembangkan Pocket Book Berbasis Pendekatan Matematika Realistik Indonesia (PMRI) Materi Bangun Ruang Sisi Datar - Drajat Friansah; Idul Adha; Rani Refianti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study is to produce a pocket book of valid and practical flat side space material based on the Indonesian realistic mathematics approach (PMRI) and determine the potential effects arising from the development of pocket books and student responses to the developed pocket books. This research is a quantitative study with the design of Research and Development (R&D). The development of this pocket book is carried out through two stages, namely the priliminary (preparation) stage and the formative evaluation stage. The results of this study indicate that the pocket book builds flat side space using the PMRI approach that is produced valid and practical. Valid drawn from the results of revision after being validated by experts based on content, construct, and language. Based on the document analysis of the results of student work during the field test, showed the final test of learning using a pocket book with PMRI approach got a very good category 43.75%, good 28.12%, Quite 15.62%, and less 12.5%, the result data the test is that the learning performed shows good potential effects. Based on the analysis of the results of student responses to the pocket book developed for the indicator of interest in the pocket book obtained 86.09% of students expressed strongly agree, material indicators 79.97% of students agreed and indicators of language 89.32% of students strongly agreed. In conclusion, pocket books developed based on the Indonesian realistic mathematics approach (PMRI) are declared valid and practical to use and have good and interesting potential effects for students. Keywords: Pocket Book Development, PMRI